Tidak Ada Unsur Pembeda Antara Perusahaan Induk Dengan Perusahaan Anak (Studi Kasus akuisisi PT Pegadaian dengan PT BRI Tbk) - Rizkiyah Silvani; Dina Triwijayanti; Sumriyah Sumriyah (International Forum of Researchers and Lecturers, 2023)
Subsidiaries are companies whose shares are controlled by other companies, Subsidiaries usually consist of groups, business units that have business fields in different fields. subsidiary companies with parent companies we are talking about PT Pegadaian with PT Bri tbk. PT Pegadaian is PT Pegadaian (Persero), the owner of the Pegadaian brand (brand) is a state-owned company that opened for the first time in Sukabumi.